THE EFFECT OF E-TICKET SANCTION ON CHANGE OF CHILDREN BEHAVIOR ON THE CASE OF TRAFFIC LAW VIOLATION IN BENGKULU CITY - Yogi Syaputra Tanjung; Lidia Br Karo; Hamzah Hatrik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
This analysis aims to provide a description so that children and parents know about the E-Ticketing regulations in traffic law. Describing E-ticketing can influence parents to prevent children from violating traffic laws in using motorized vehicles. The method used in this study was an empirical legal research method with the sociological juridical research approach. In this study, the data used were primary and secondary data. Then the data were analyzed qualitatively by means of deductive-inductive thinking. From the results of the research conducted by the writer, it can be concluded that: (1) There are several factors behind the children committing traffic violations, namely as follows: (a) the lack of children’s knowledge of traffic rules. In most cases, the children did not have a driving license, therefore they did not have enough understanding regarding the applicable traffic rules, and (b) the lack of supervision and ignorance of parents so that they allow, even facilitate, children to use motorized vehicles, this is also a major factor in the increase in traffic violations and accidents by children in Bengkulu City. (2) With the implementation of E-Ticket sanction with a maximum fine, Investigators at the Directorate of Traffic of Bengkulu Police Department have carried out their roles properly and have been in accordance with the SOPs (Standard Operating Procedures). Moreover, they also have carried out their functions as maintainers of Security, Safety, Order, and Traffic Smoothness. Thus they can take action against traffic violations by children as a whole. Furthermore, from the process of taking action against violations by using the E-Ticketing, besides being able to reduce the number of traffic violations by children, parents can also take on the role of supervisors and mentors for their children, so that parents are able to change the behavior of children to be more aware of traffic laws at a later time.